1961
DOI: 10.1590/s0071-12761961000100022
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição para o conhecimento da ''saúva mata pasto" Atta bisphaerica Forel, 1908

Abstract: (1) Trabalho apresentado a XIII Reunião Anual da Sociedade Brasileira Para o Progresso da Ciência, realizada de 9 a 15 de julho de 1961, em Poços de Caldas, Minas Gerais.(2) Recebido para publicação em 31/10/1961.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In general, when these ants prepare substrate to inoculate symbiont fungus, they do not cut vegetal fragments into pieces as small as those from leaf‐cutters ( Mariconi , 1970; Fowler et al., 1986). The latter ants transform the vegetal pieces into progressively smaller pieces until they are in the form of pulp ( Andrade et al., 2002), while in A. bisphaerica the mean length of grass pieces was 6 mm ( Zamith et al., 1961). Naturally, these differences are perceptible in the morphology of both the worker and the fungus garden and also in the cutting behaviour ( Fowler et al., 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, when these ants prepare substrate to inoculate symbiont fungus, they do not cut vegetal fragments into pieces as small as those from leaf‐cutters ( Mariconi , 1970; Fowler et al., 1986). The latter ants transform the vegetal pieces into progressively smaller pieces until they are in the form of pulp ( Andrade et al., 2002), while in A. bisphaerica the mean length of grass pieces was 6 mm ( Zamith et al., 1961). Naturally, these differences are perceptible in the morphology of both the worker and the fungus garden and also in the cutting behaviour ( Fowler et al., 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Foraging activity is performed through the use of physical and chemical trails ( Weber , 1972; Cedeño‐León , 1984; Fowler , 1978), which rarely surpass 20 m in length with 3–5 cm of width ( Mariconi et al., 1963) and the activity in these trails is most intense between 15 and 20°C ( Amante , 1972). Like other Atta species, the nuptial flight occurs with the greatest intensity in the months of October and November ( Zamith et al., 1961) and the losses to predators were 59% during the pre‐claustral phase in queens in areas of no mature colonies ( Fowler , 1987). This author observed that c. 89% of all founding queens were killed in areas with mature colonies.…”
Section: Introductionmentioning
confidence: 99%
“…Dead fungus gardens are attacked by alien fungi and invaded by invertebrates and in many cases ants use chambers with dead gardens to deposit other waste materials (i.e. Bruch, 1917;Zamith et al, 1961;Moser, 1962;Mariconi, 1970;Weber, 1972;Zolessi and Abenante, 1973;Zolessi and González, 1974;Jonkman, 1980;Coutinho, 1984;Rabeling et al, 2007). In one case it has been reported that the attack by other fungus resulted in a dead garden covered by a resistant fungal layer that consolidates the whole structure (Zamith et al, 1961).…”
Section: Fungus Gardens Of An Attini Ancestor?mentioning
confidence: 99%
“…Bruch, 1917;Zamith et al, 1961;Moser, 1962;Mariconi, 1970;Weber, 1972;Zolessi and Abenante, 1973;Zolessi and González, 1974;Jonkman, 1980;Coutinho, 1984;Rabeling et al, 2007). In one case it has been reported that the attack by other fungus resulted in a dead garden covered by a resistant fungal layer that consolidates the whole structure (Zamith et al, 1961). Such dead gardens with resistant outer layers, probably more preservable, are also a possibility to be considered when attempting to interpret the wall and the morphological differences among the Cretaceous rhizolith balls.…”
Section: Fungus Gardens Of An Attini Ancestor?mentioning
confidence: 99%